(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
Crime is an old social problem that has accompanied Man since his existence, and human efforts have not succeeded in eradicating it or even reducing it. The seriousness of crime and recidivism comes from its opposition to human feelings and from the damages which it causes to the public and private interests, and also from the huge material and moral losses which it causes. These losses appear in the exorbitant costs required to be combated by the development of security services, penal and correctional institutions, and human energies that go to waste, that because it could be exploited in other areas that contribute to the development and construction of society, instead of deviating towards crime and threatening security and stability.